POLA MAKAN DAN INDEKS KENYANG PADA CAPLAK BETINA Rhipicephalus sanguineus (ACARI, IXODIDAE) - ., Leliana (Jurnal Edukasi dan Sains Biologi, 2014)
This aims of the research is to know feeding pattern, and engorgement index in female Rhipicephalus sanguineus. Feeding experiment were designed using the following female-male ratio 1:1. At same time every day up to detachment the body length, width and depth of females were measured using a caliper to the determine of body volume. The result of this research indicates that rate of engorgement indices in females (1:1 ratio) increased with increasing duration of attachment (P< 0.05) and the relationship between duration of tick attachment was above 90%. A significant increase in body cuticle extensibility occurs following copulation. Keywords: Rhipicephalus sanguineus, engorgement index, duration of attachment.